Expectations and Experiences of Couples Receiving Therapy Through Videoconferencing: A Qualitative Study - Kysely, Andrea; Bishop, Brian; Kane, Robert; Cheng, Maryanne; De Palma, Mia; Rooney, Rosanna (Frontiers in Psychology, 2020)
Videoconferencing is an emerging medium through which psychological therapy, including relationship interventions for couples, can be delivered. Understanding clients’ expectations and experiences of receiving therapy through this medium is important for optimising future delivery. This study used a qualitative methodology to explore the expectations and experiences of couples throughout the process of the Couple CARE program, which was delivered through videoconferencing. Fifteen couples participated in semi-structured interviews during the first and last sessions of the intervention. The interviews were conducted using the iChat program, with the therapist conducting the first interview and an external interviewer conducting the second. Thematic analysis was used to identify themes from the interview transcripts. Five themes were identified from the pre-therapy interviews, reflecting couples’ initial impressions and expectations: new experience, comparison, practical aspects, connection and dynamics, and distance and space. Couples’ experiences were explored in the eight themes from the post-therapy interviews: technicalities, the idea of ‘distance’, satisfaction and comfort, confidentiality, comparisons, new experience, expectations change, and working alliance. Overall, the present study found that couples experienced a positive shift in expectations. Despite some initial concerns regarding the therapist’s ability to empathise over a screen and the potential for the technology to break down, many clients noted that videoconferencing allowed them to become fully immersed in the therapeutic process. In fact, many couples felt that videoconferencing created an element of ‘distance’ from the therapist that allowed them to feel a greater sense of control and comfort. Couples consistently described being able to effectively connect with the therapist, and that the video actually enhanced the therapeutic alliance, due to a greater perceived focus on therapy processes. Overall, despite some initial concerns, the majority of couples found the videoconferencing experience to be beneficial and positive.